Heavy metals pollution in surface waters of Pakistan - Azizullah, Azizullah; Taimur, Nadia; Khan, Sarzamin; Häder, Donat-Peter (Springer International Publishing, 2021)
Fresh water resources in Pakistan are under immense duress due to uncontrolled pollution from industries, municipalities and agriculture runoffs. Microbial and chemical pollutants released into water bodies have intensified with an increase in anthropogenic activities rendering the water unfit for drinking. Of the chemical pollutants heavy metals are the most toxic and persistent contaminants that are ubiquitously disseminated in the freshwater resources throughout the country. Fresh water lakes and rivers are the most vulnerable to contamination with metal pollutants such as arsenic, lead, cadmium, chromium and nickel, emanating from untreated industrial, municipal and domestic waste. Heavy metals in concentrations above permissible limits severely alter water quality and serve as toxins with severe implications for human health. These pollutants are of major environmental concerns due to their persistence in the environment and high potential to bioaccumulate in aquatic organisms, plants, animals and human tissues posing a serious threat to the entire biosphere. The abundant occurrence of heavy metals in aquatic ecosystems is also deleterious for the biodiversity of aquatic organisms causing a severe decline in the population and diversity of freshwater fish and other aquatic species. In aquatic organisms, particularly fish, heavy metals bioaccumulate over a million-fold in metabolically active organs such as gills, liver, skin, kidneys and muscles and consequently become part of the food chain. Frequent consumption of contaminated plant-based food, freshwater fish and other seafood has endangered lives of the consumers. Data extracted from research studies conducted in the last two decades has revealed critical increase in heavy metal pollution in freshwater ecosystems particularly in rivers largely due to unabated human interventions. In addition to acute water scarcity, continuous disposal of pollutants in water bodies has further worsened the water crisis in Pakistan. Consequently, the majority of the population dependent on freshwater resources for their livelihood and drinking water needs is deprived of access to reliable, safe and clean drinking water. This chapter summarises the current levels of heavy metal concentrations in freshwater resources i.e. rivers and lakes in Pakistan with special emphasis on the impact of major pollutants and subsequent effects on fish, agriculture and human health.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bioaccumulation of toxic metals; Contaminated fish and aquatic plants; Heavy metal poisoning; Heavy metals; Industrial and agricultural effluents; Polluted lakes and rivers; Unsafe drinking water and health hazards; Water pollution